2007
DOI: 10.1111/j.1349-7006.2007.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CD147 in regulation of multidrug resistance to P‐gp substrate drugs and in vitro invasion in breast cancer cells

Abstract: Multidrug resistant (MDR) cancer cells overexpressing P-glycoprotein (P-gp) display variations in invasive and metastatic behavior. We aimed to clarify the mechanism(s) underlying this observation and transfected vectors carrying CD147, a glycoprotein enriched on the surface of tumor cells that stimulates the production of matrix metalloproteinases (MMPs), and specific shCD147 into MCF7 and MCF7/Adr cells, respectively. Using quantitative real-time polymerase chain reaction and Western blot, we found that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 27 publications
6
43
0
Order By: Relevance
“…Previous reports demonstrated that continued activation of AKT was related to the resistance to conventional chemotherapeutic agents (55)(56)(57)(58). To determine whether the MDR reversal activity of lapatinib was related to the change of AKT (D) Grayscale ratios of MRP1/GAPDH were analyzed with ImageJ.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that continued activation of AKT was related to the resistance to conventional chemotherapeutic agents (55)(56)(57)(58). To determine whether the MDR reversal activity of lapatinib was related to the change of AKT (D) Grayscale ratios of MRP1/GAPDH were analyzed with ImageJ.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of cells to VCR was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay as described previously (17). Briefly, cells in the logarithmic phase were seeded in 96-well plates at a density of 1x10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…The multidrug chemosensitivity of cells under investigation and their corresponding controls was assessed as described previously. (13) The relative inhibitory rate of cell growth by different concentrations of ADM was calculated according to the following formula:…”
Section: Methodsmentioning
confidence: 99%